Find the square root(s) of 2 + i , (where i = − 1 ) in the form x + y i , then give your answer as the value of the expression below.
( ∑ x 2 ) × ( ∑ y 2 )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Can you expand on that a little bit more please
To solve the square root of 2+ i , firstly you write the square of your hypothetical answer and equate the real and imaginary parts, as follows: ( x + y i ) 2 = x 2 - y 2 +2 x y i , so x 2 - y 2 = 2 ( 1) and 2 x y i =1 (2 ). Rearranging (2 ) gives, y = 2 x 1 which we substitute back into equation ( 1): x 2 - 4 x 2 1 = 2. Multiply by 4 x 2 and rearranging leads to 4 x 4 - 8 x 2 -1 = 0. This is a quadratic in disguise, so let t = x 2 and solve 4 t 2 - 8 t -1 = 0 (and square root the results) to produce the following 2 roots: x 1 = 1 + 2 1 5 and x 2 = 2 1 5 − 1 i . Substitute the value of x 2 into equation (*1) yields: y 1 = 2 1 5 − 1 and y 2 = 1 + 2 1 5 i . Now ∑ x 2 = 2 + 5 and ∑ y 2 = 5 -2. The answer is ∴ ( 5 +2)( 5 -2) = 1
Doesn’t the equation 4x^4-8x^2-1=0 have four solutions? X1, X2 but also X3=-X1 and X4=-X2? If I didn’t mistake the calculations, the sum of x^2 is 4 and the sum of y^2 is -4, so the result is -16
Problem Loading...
Note Loading...
Set Loading...
I believe there is much simpler solution. From the equations, we get that roots are z and -z. (x,-x) and (y,-y) Summation x^2 = 2x^2 Summation Y^2 = 2y^2.
Therefore, the question simplifies as 4 x^2 y^2 = 4/4 = 1.